Employee Performance Determinants: The Roles of Transformational Leadership, Organizational Commitment, and Loyalty - Ratnawita Ratnawita; Widya Nengsih; Prihatina Jati; Dewi Listiorini; Indri Astuti (Lembaga Riset dan Inovasi Al-Matani, 2026)
Employee performance is a crucial determinant of organizational competitiveness, particularly in the financial services industry. Although previous studies have established that transformational leadership, organizational commitment, and employee loyalty contribute to enhanced employee performance, empirical evidence within the Indonesian financing sector remains limited. This study aims to examine the influence of transformational leadership, organizational commitment, and employee loyalty on employee performance at PT. FIF Group, Tlogosari Branch, Semarang. A quantitative explanatory research design was employed using a census sampling technique involving all employees of the organization. Data were collected through a structured questionnaire and analyzed using multiple linear regression. The findings reveal that transformational leadership, organizational commitment, and employee loyalty each have a positive and significant influence on employee performance. Furthermore, these variables collectively provide substantial explanatory power in predicting employee performance. This study contributes to the human resource management literature by extending empirical evidence from the Indonesian financing industry and underscores the importance of strengthening transformational leadership practices, fostering organizational commitment, and enhancing employee loyalty to achieve sustainable organizational performance.